The effects of a 20-week exercise program on blood-circulating biomarkers related to brain health in overweight or obese children: The ActiveBrains project - María Rodriguez-Ayllon; Abel Plaza-Florido; Andrea Mendez-Gutierrez; Signe Altmäe; Patricio Solis-Urra; Concepción M. Aguilera; Andrés Catena; Francisco B. Ortega; Irene Esteban-Cornejo (Journal of Sport and Health Science, 2023)
Background: Emerging research supports the idea that exercise positively affects neurodevelopment. However, the mechanisms linking exercise with brain health are largely unknown. We aimed to investigate the effect of exercise on (a) blood biomarkers selected based on previous evidence (brain-derived neurotrophic factor, β-hydroxybutyrate (BHB), cathepsin B (CTSB), kynurenine, fibroblast growth factor 21 (FGF21), soluble vascular cell adhesion molecule-1 (sVCAM-1)); and (b) a panel of 92 neurology-related proteins (discovery analysis). We also investigated whether changes in these biomarkers mediate the effects of exercise on brain health (hippocampal structure and function, cognitive performance, and mental health). Methods: We randomized 81 overweight/obese children (10.1 ± 1.1 years, 41% girls) into 2 groups: either 20 weeks of aerobic plus resistance exercise or control. Candidate biomarkers were assessed using enzyme-linked immunosorbent assay (ELISA) for kynurenine, FGF21, and CTSB; colorimetry for β-hydroxybutyrate; and XMap for brain-derived neurotrophic factor and soluble vascular cell adhesion molecule-1. The 92 neurology-related proteins were analyzed by an antibody-based proteomic analysis. Results: Our intervention had no significant effect on candidate biomarkers (all p > 0.05). In the discovery analysis, a reduction in circulating macrophage scavenger receptor type-I was observed (standardized differences between groups = –0.3, p = 0.001). This effect was validated using ELISA methods (standardized difference = –0.3, p = 0.01). None of the biomarkers mediated the effects of exercise on brain health. Conclusions: Our study does not support a chronic effect of exercise on candidate biomarkers. We observed that while chronic exercise reduced the levels of macrophage scavenger receptor type-I, it did not mediate the effects of exercise on brain health. Future studies should explore the implications of this novel biomarker for overall health.